Angina pectoris and sinus of Valsalva aneurysm: a rare manifestation of an uncommon disease - Simonavičius, Justas; Jarašūnienė, Dalia (Acta medica Lituanica, 2019)
Sinus of Valsalva aneurysm is an uncommon finding. The present paper describes a case report of a 57-year-old female patient who developed angina pectoris due to the left sinus of Valsalva aneurysm. Clinical presentation, localization, unruptured status and concomitant coarctation of the aorta make the case presented in this document extremely rare and interesting. Current knowledge about the disease is briefly discussed.
Keywords: angina pectoris; sinus of Valsalva aneurysm; congenital heart disease; aortic coarctation